Government Leadership and Organizational Culture: A study on Regional Aparatus In Jambi City - Tri Raharjanto (Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to determine the effect of government leadership, organizational culture and government bureaucracy on the performance of Regional Apparatus for Managing Regional Original Revenue managers in Jambi City. This research uses a quantitative approach with the post-positivism paradigm method, which is looking for facts and the relationship between the variables and this approach also explores the causal relationship between the variables. The results of the study found Government Leadership had a positive and significant effect on the Performance of Regional Apparatus for Managing Regional Original Revenue Managers in Jambi City, Organizational Culture had a positive and significant impact on the Performance of Regional Apparatus for Managing Regional Original Revenue Managers in Jambi City, Government Bureaucracy had a positive and significant effect on the Performance of Regional Apparatus for Managing Regional Original Revenue Managers in Jambi City and finally Leadership Governance, Organizational Culture and Government Bureaucracy together have a positive and significant impact on the performance of Regional Apparatus for Managing Regional Original Revenue managing in Jambi City.